A colônia de Santa Isabel e seus imigrantes (1847-1889) - Raasch, Silas (2010)
This present Dissertation - The Colony of Santa Isabel and its immigrants – intend to discuss the installation and aspects of life of Teutons immigrants in the colony of Santa Isabel, the first founded in the Espírito Santo, in the period between 1847 and 1889. To this end, we compare information found in the reports of the President of the Province, reports of the consuls of foreign countries, documents relating to the administration of the colony, records of marriages and criminal‘s process. The research itself has the intention to understand how foreigners, and their descendants, (re)build their existences in a land is completely different from what they were accustomed. We also try to understand, as some spaces of sociability were marked by differences of the group that settled there. Under the name of settler homogenizing (immigrant), or more specifically German settler, who remained strong religious differences reflected in various aspects of life such persons, including territorial, marking the trace of the location as "territory" of Catholics and Protestants. We also observe that the principle of religious tolerance has guided the actions of officers in the Province and the Empire, probably given the economic importance credited for the development of immigration. That means more than installing a Teuta‘s Colony, Santa Isabel is the cultural dynamic image of the "Germans" in the Espírito Santo.